A Comprehensive Examination of Bandgap Semiconductor Switches. (25th September 2021) - Siva Subramanian, S.; Saravanakumar, R.; Ganthia, Bibhu Prasad; Kaliappan, S.; Beyan, Surafel Mustefa; Mallick, Maitri; Mohanty, Monalisa; Pavithra, G.
Abstract : Improvements in the material characteristics of bandgap semiconductors allow the use of high-temperature, high-voltage, and fast switch rates in power devices. Another good reason for creating new Si power converter devices is that previous models perform poorly. The implementation of novel power electronic converters means high energy efficiency but a more logical use of electricity. At this moment, titanium dioxide and gallium nitride are the most prospective semiconductor materials because of their great features, established technology, and enough supply of raw components. This study is focused on providing an in-depth look at recent developments in manufacturing Si-C- and high-powered electronic components and showcasing the whole scope of the newly developing product generation.